Paper 74: Psychopathology and Volitional Instability: Who should we be operating on?. Issue 7 (30th July 2022) - Duchman, Kyle; Cohen, Brian; Wolf, Brian; Bishop, Julie; Baumgarten, Keith; Shoulder, MOON; Brophy, Robert; Hettrich, Carolyn; Dunn, Warren
Objectives: There has been a hesitation by surgeons to operate on shoulder instability patients with maladaptive psychopathological traits, especially those with volitional instability, as these may portend a poor prognosis. The purpose of this study was to investigate the prevalence of maladaptive psychopathological traits, volitional instability, and their effect on two-year outcomes in patients undergoing shoulder stabilization surgery. Methods: A prospective multi-center cohort study led by the Multicenter Orthopaedic Outcomes Network (MOON) Shoulder Group targeted all subjects having surgical shoulder stabilization and collected patient-reported outcomes at baseline and at two years postoperatively. Psychopathological traits were assessed using the Personality Assessment Screener (PAS), a validated personality assessment tool. Longitudinal analyses were performed using multivariable regression models to determine predictors of two-year outcomes adjusting for confounders measured at index such as age, sex, smoking, BMI, volitional instability, and intraarticular pathology. Results: The cohort (n = 890) was 80% male with a median age of 21.5 years. The prevalence of psychopathological traits was 20%. While all patients improved between baseline and 2 years, with adjusted analyses, the presence of maladaptive psychological traits present at the time of index surgery were predictive of lower WOSI (p = 0.001), ASES (p = 0.016), SANE (p = 0.03), and SF-36 MCS (p = 0.001) scores as well as a higher risk of failure (p = 0.04) at two years. As a main effect, volitional instability was not a predictor of WOSI, ASES, SANE, SF-36 or failure at two years. However, all models allowed for the interaction between volitional instability and the PAS, and this interaction was significant for WOSI (p = 0.006), SANE (p = 0.03), and SF-36 MCS (p = 0.003) scores at two years. In other words, the effect of volitional instability on the WOSI, SANE, and SF-36 MCS scores depends on the value of the PAS, and with high PAS scores it is associated with worse outcomes. This data is depicted in Figures 1-3. Conclusions: While all patients improved, the presence of maladaptive psychopathological traits at the time of index surgery was a predictor of poorer outcomes at two years. Voluntary dislocators did similarly as non-voluntary dislocators up to a PAS score of ˜ 20, where above this they had worse WOSI, SANE, SF-36 MCS and higher failure rates at 2 years post-operatively. Figure 1. Adjusted effects of PAS score and volitional instability on WOSI score at 2 years Figure 2. Adjusted effects of PAS score and volitional instability by gender on predicted MCS Score at two years Figure 3. Adjusted effects of PAS score and volitional instability on probability of failure